Comparable response of wild rodent gut microbiome to anthropogenic habitat contamination. Issue 14 (27th May 2021) - Lavrinienko, Anton; Hämäläinen, Anni; Hindström, Rasmus; Tukalenko, Eugene; Boratyński, Zbyszek; Kivisaari, Kati; Mousseau, Timothy A.; Watts, Phillip C.; Mappes, Tapio
Abstract: Species identity is thought to dominate over environment in shaping wild rodent gut microbiota, but it remains unknown whether the responses of host gut microbiota to shared anthropogenic habitat impacts are species‐specific or if the general gut microbiota response is similar across host species. Here, we compare the influence of exposure to radionuclide contamination on the gut microbiota of four wild mouse species: Apodemus flavicollis, A .  sylvaticus, A .  speciosus and A .  argenteus . Building on the evidence that radiation impacts bank vole ( Myodes glareolus ) gut microbiota, we hypothesized that radiation exposure has a general impact on rodent gut microbiota. Because we sampled ( n  = 288) two species pairs of Apodemus mice that occur in sympatry in habitats affected by the Chernobyl and Fukushima nuclear accidents, these comparisons provide an opportunity for a general assessment of the effects of exposure to environmental contamination (radionuclides) on gut microbiota across host phylogeny and geographical areas. In general agreement with our hypothesis, analyses of bacterial 16S rRNA gene sequences revealed that radiation exposure alters the gut microbiota composition and structure in three of the four species of Apodemus mice. The notable lack of an association between the gut microbiota and soil radionuclide contamination in one mouse species from Fukushima ( A .  argenteus ) probably reflects host "radiation escape" through its unique tree‐dwelling lifestyle. The finding that host ecology can modulate effects of radiation exposure offers an interesting counterpoint for future analyses into effects of radiation or any other toxic exposure on host and its associated microbiota. Our data show that exposure to radionuclide contamination is linked to comparable gut microbiota responses across multiple species of rodents.